Synergizing Education, Family, and Community in Empowering Kampung KB for Drug Abuse Prevention Among Youth in Aceh - Muhajir, Muhajir (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
The abuse of narcotics and other addictive substances poses a serious threat to the sustainability of human resource development, particularly in Aceh Province, where adolescents are highly vulnerable. This study aims to analyze the implementation of the Family Planning Village (Kampung KB) empowerment program in fostering a drug-free generation by emphasizing the synergy among education, family, and community roles. This qualitative research was conducted in Banda Aceh and Bireun, utilizing data collected through interviews, focus group discussions (FGDs), and program documentation. The findings indicate that active involvement of schools, families, youth groups, and community leaders in the Kampung KB program has fostered a social environment conducive to drug abuse prevention. Youth-driven campaign innovations, integration of anti-drug education into formal curricula, and participation of religious and traditional leaders have been effective in strengthening community resilience. However, the program faces challenges, including limited family participation, intersectoral coordination barriers, and social stigma. This study recommends strengthening family and cadre capacity, enhancing cross-sector collaboration, and conducting regular monitoring and evaluation to ensure the effectiveness of community-based drug prevention interventions.